PENGARUH MODEL STUDENT FACILITATOR AND EXPLAINING TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR - Astutiningsih, Yuli; Supratno, Haris; Siswanto, M. Bambang Edi (IJPSE : Indonesian Journal of Primary Science Education, 2020)
The research objective was to describe the effect of using the Student Facilitator and Explaining model of learning on thematic learning at SDN Balongbesuk, Diwek, Jombang. The experimental method used in this study, and the research design used the Noneequivalent Control Group. Grade IV students were used as subjects in this study. Data were collected by observation, interviews, and tests. The t-test formula is used to analyze the data results. It is shown by the results of the research on learning mechanisms to be more effective by using the Student Facilitator And Explaining learning model, because it participates and engages students directly in the learning mechanism. Make students competent to express ideas or ideas to their friends. The use of the Student Facilitator And Explaining model can increase students' insight while learning, direct student involvement in the learning mechanism, because it can increase student learning outcomes.